2008
DOI: 10.1111/j.1939-1676.2008.0188.x
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Converts Acute Vagally Associated Atrial Fibrillation to Sinus Rhythm in German Shepherd Dogs with Inherited Arrhythmias

Abstract: Background: Lidocaine is most frequently used to treat ventricular arrhythmias. However, lidocaine may have an antiarrhythmic effect for certain supraventricular arrhythmias.Hypothesis: We hypothesized that lidocaine would be effective in converting experimentally induced atrial fibrillation (AF) to sinus rhythm and that a decrease in the dominant frequency (DF) and an increase in the organization as judged by the spectral entropy (SE) would occur over the course of the conversion.Animals: Seven German Shepher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Systemic administration of lidocaine, a local anesthetic, is commonly used in dogs for the management of cardiac arrhythmias [40]. Studies have found that the intraoperative administration of lidocaine can significantly reduce the MAC of volatile anesthetic in rabbits, cats, and dogs [1], as well as in horses [13].…”
mentioning
confidence: 99%
“…Systemic administration of lidocaine, a local anesthetic, is commonly used in dogs for the management of cardiac arrhythmias [40]. Studies have found that the intraoperative administration of lidocaine can significantly reduce the MAC of volatile anesthetic in rabbits, cats, and dogs [1], as well as in horses [13].…”
mentioning
confidence: 99%
“…Atrial fibrillation was likely induced by increased vagal tone from sedation and general anaesthesia, the dog's underlying myocardial disease, and catheter manipulation within the right atrium and coronary sinus, triggering supraventricular ectopy that evolved into atrial fibrillation. Treatment of vagally induced acute atrial fibrillation with lidocaine and class Ia antiarrhythmics has been described and similarly was effective in the six dogs here (Wang et al 1993, Pariaut et al 2008. The single dog that experienced worsening ventricular arrhythmias and ultimately succumbed to cardiac arrest while hospitalized had a history of malignant ventricular ectopy.…”
Section: Resultsmentioning
confidence: 96%
“…, Pariaut et al . ). The single dog that experienced worsening ventricular arrhythmias and ultimately succumbed to cardiac arrest while hospitalized had a history of malignant ventricular ectopy.…”
Section: Discussionmentioning
confidence: 97%
“…Mepivicaine is a fast sodium-channel blocker closely related to lidocaine. There is evidence that the use of lidocaine is successful in converting vagally-induced atrial fibrillation in dogs 23 and atrial-selective sodium-channel blockers are being investigated as a novel pharmacologic treatment for conversion of atrial fibrillation. 24 Thus, it is not unreasonable to suppose that the infusion of mepivicaine acted directly on the traumatized atrial myocardium to modify conductivity and allow cardioversion.…”
Section: Discussionmentioning
confidence: 99%